2011
DOI: 10.1002/cbf.1833
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E supplementation modulates gingival crevicular fluid lipid peroxidation and antioxidant levels in patients with orthodontic tooth movement

Abstract: The aim of this study was to investigate the levels of the oxidant and antioxidant changes in orthodontic tooth movement and the effects of vitamin E on these parameters. For this purpose, 50 orthodontic patients (aged 13-18 years) required non-extracted treatment were divided randomly into the following groups: Control and Vitamin E. Same pre-adjusted appliances were applied to all patients, and vitamin E (300 mg day(-1)) was given during 1 month in vitamin E group. Gingival crevicular fluid was collected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…After day 3, movement for group 1 reduced, while for group 2, this continued to increase until day 7. force stimulate the production of reactive oxygen species and free radicals, which contribute to cellular and tissue damage, especially damaging lipid peroxidation chains 22 . Vitamin E is a strong biological antioxidant that has several functions: scavenges free radicals, which inhibit lipid peroxidation and inflammation; protects ischemic tissue and hypoxia; provides immunostimulation 11,23 . Norazlina et al observed the effect of vitamin E supplementation on bone metabolism in mice treated with nicotine.…”
Section: Resultsmentioning
confidence: 99%
“…After day 3, movement for group 1 reduced, while for group 2, this continued to increase until day 7. force stimulate the production of reactive oxygen species and free radicals, which contribute to cellular and tissue damage, especially damaging lipid peroxidation chains 22 . Vitamin E is a strong biological antioxidant that has several functions: scavenges free radicals, which inhibit lipid peroxidation and inflammation; protects ischemic tissue and hypoxia; provides immunostimulation 11,23 . Norazlina et al observed the effect of vitamin E supplementation on bone metabolism in mice treated with nicotine.…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia and compression caused by orthodontic force stimulate the production of reactive oxygen species and free radicals, which contribute to cellular and tissue damage, especially damaging lipid peroxidation chains 22 . Vitamin E is a strong biological antioxidant that has several functions: scavenges free radicals, which inhibit lipid peroxidation and inflammation; protects ischemic tissue and hypoxia; provides immunostimulation 11,23 . Norazlina et al observed the effect of vitamin E supplementation on bone metabolism in mice treated with nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that vitamin E has anti-inflammatory properties, which helps suppress damaging effects of oxygen free radicals in cells during bone formation 10 . Previous studies carried out by Esenlik et al and Xu et al suggest that vitamin E supplementation may alter cytokine production; vitamin E supplement maintains normal bone remodelling in young animals and increases bone mass by decreasing the concentration of free radicals which suppress bone formation 11,12 .…”
Section: Introductionmentioning
confidence: 98%
“…Hypoxia and compression caused by orthodontic force stimulate the production of reactive oxygen species and free radicals, which contribute to cellular and tissue damage, especially damaging lipid peroxidation chains 18 . Vitamin E is a strong biological antioxidant that has several functions: scavenges free radicals, which inhibit lipid peroxidation and inflammation; protects ischemic tissue and hypoxia; provides immunostimulation 11,19 . Norazlina et al observed the effect of vitamin E supplementation on bone metabolism in mice treated with nicotine.…”
Section: Discussionmentioning
confidence: 99%